Systematic Review of Cost Overrun Research in the Developed and Developing Countries - Bin Ismail, Mohamad Zahierruden; Bin Mohamad Ramly, Zuhaili; Bin Adul Hamid, Razali (International Journal of Sustainable Construction Engineering and Technology, 2021)
For decades, reputation of the construction industry has been tainted by poor cost performance caused by project cost overrun. In addition, studies by scholars worldwide have also found cost overrun to be more serious in developing countries compared to the developed countries. Despite the numerous researches addressing the issue of cost overrun in the construction industry through the years, the issue remains. Acknowledging that maintaining good cost performance is a key factor of project success and that the issue has persisted for decades, this study aims to explore the distinction of cost overrun studies that has been conducted between developed nations and developing nations. In achieving this aim, a systematic literature review is performed by following the integrative steps of PSALSAR (Protocol, Search, Appraisal, Synthesis, Analysis and Report) and PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) for screening and selecting the retrieved studies. The synthesis and screening of literatures have yielded with 152 articles which are then classified into their countries, developed countries (44) and developing countries (108). The results indicated a significant difference in the domain of research on cost overrun between the 2 nations. Despite the numerous studies on cost overrun in the developing nations compared to developed nations, the majority of the studies are not directed to any specific type construction while developed nations have moved forward to focus on more specific projects. The project with the highest attention in the developed nations is transport infrastructure construction projects, particularly rail infrastructure projects. The findings of this study have shown that there have been broad studies conducted on cost overrun in both developing nations and developed nations. However, there is a slight lacking in comprehensiveness of cost overrun studies in the developing nations, perhaps future studies on cost overrun in developing nations can be directed to more specific areas of construction projects such as those that have been performed by researchers of the developed nations